An updated systematic review of esthetic grading tools in postmastectomy breast reconstruction. Issue 5 (3rd January 2023) - Stern, Carrie; Kim, Leslie N.; Plotsker, Ethan; Boyce, Lindsay; Dayan, Joseph; Nelson, Jonas A.
Abstract: Background and Objectives: We ascertained whether a validated esthetic grading tool for breast reconstruction had been developed and widely adopted since the last published systematic review on the topic from 2015. Methods: We performed a systematic review identifying all studies using a grading tool to assess breast reconstruction, using search terms associated with all types of breast surgery and outcomes research. Articles were assessed for patient number, validated scale use, assessor type and training, assessor blinding, assessment method, scoring system type, type and timing of reconstruction, and usage of corroborating scales. Results: Of 2809 articles screened, 148 met the criteria. Only 3 used a validated tool, the Esthetic Items Scale. Most used study‐only tools ( n  = 111) or unvalidated tools ( n  = 28). The most used unvalidated tool was the Garbay/Lowery 5‐subscale rubric. Unanchored Likert scales were the most common subjective tool; two‐dimensional images were the most used medium. Surgeons, patients, and nurses were the most common assessors. Twenty percent of studies used corroborating scales. Conclusions: In the absence of a validated esthetic grading tool for breast reconstruction, researchers continue to rely on unvalidated scales. The only validated scale available is used infrequently and only validated among physicians. A validated, reliable, simple grading tool with clinical and scholastic relevance is needed.